FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Slamet Ribut Wahyuning, 10.05.51.0067 (Students Journal of Economic and Management, 2014)
This study aims to examine the factors that affect stock returns on companies listed on the Stock Exchange 2009-2011.The results showed that the variables of Economic Value Added (EVA), which has a positive and significant impact on stock returns. While the Return On Assets (ROA), Current Ratio (CR), Operating Leverage, Debt to Equity Ratio (DER) hasnât significant effect. This suggests that investors see that companies are able to provide economic value added demand by investors. So the company that possess the Economic Value Added (EVA), which will increase the return of its shares. Keywords: Return On Asset (ROA), Current Ratio (CR), Operating Leverage, Economic Value Added (EVA), Debt to Equity Ratio (DER), and Stock Return